2018
DOI: 10.1158/2159-8290.cd-18-0099
|View full text |Cite
|
Sign up to set email alerts
|

STK11/LKB1 Mutations and PD-1 Inhibitor Resistance in KRAS-Mutant Lung Adenocarcinoma

Abstract: is the most common oncogenic driver in lung adenocarcinoma (LUAC). We previously reported that (KL) or (KP) comutations define distinct subgroups of -mutant LUAC. Here, we examine the efficacy of PD-1 inhibitors in these subgroups. Objective response rates to PD-1 blockade differed significantly among KL (7.4%), KP (35.7%), and K-only (28.6%) subgroups ( < 0.001) in the Stand Up To Cancer (SU2C) cohort (174 patients) with -mutant LUAC and in patients treated with nivolumab in the CheckMate-057 phase III trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
1,080
8
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,241 publications
(1,140 citation statements)
references
References 57 publications
46
1,080
8
6
Order By: Relevance
“…Lung adenocarcinomas with STK11 mutations had relatively lower levels of infiltrating CD4+/CD8+ T‐cells and PD‐L1 expression indicating a muted immune response . Furthermore, STK11 alterations in KRAS ‐mutant lung adenocarcinoma were identified as a major driver of primary resistance to a checkpoint inhibitor . In agreement with these previous findings, the current study showed that STK11 mutations were related to an inferior response to atezolizumab.…”
Section: Discussionsupporting
confidence: 89%
“…Lung adenocarcinomas with STK11 mutations had relatively lower levels of infiltrating CD4+/CD8+ T‐cells and PD‐L1 expression indicating a muted immune response . Furthermore, STK11 alterations in KRAS ‐mutant lung adenocarcinoma were identified as a major driver of primary resistance to a checkpoint inhibitor . In agreement with these previous findings, the current study showed that STK11 mutations were related to an inferior response to atezolizumab.…”
Section: Discussionsupporting
confidence: 89%
“…45,48 That being said, there are several other genetic alterations that correlate with PD-L1 expression, TMB and ICI-efficacy in NSCLC, which could therefore also aid prognostication and therapeutic decisions regarding lung cancer immunotherapy. 51 In our dataset, we observed a negative effect of STK11 mutations on benefit of NSCLC patients from immunotherapy, but a positive influence of KRAS/TP53 co-mutations (Fig. [48][49][50] For KRAS-mutant ADC, co-occurring deleterious TP53 mutations (357/1,006, 36% in our cohort) confer higher response rates to checkpoint blockade, while mutational inactivation of STK11 (8% in our cohort) promotes ICI resistance in patients and syngeneic murine models.…”
Section: Discussionmentioning
confidence: 54%
“…[48][49][50] For KRAS-mutant ADC, co-occurring deleterious TP53 mutations (357/1,006, 36% in our cohort) confer higher response rates to checkpoint blockade, while mutational inactivation of STK11 (8% in our cohort) promotes ICI resistance in patients and syngeneic murine models. 51 On the other hand, oncogene-driven NSCLC harboring EGFR-/BRAF−/MET-mutations or ALKrearrangements generally have lower TMB levels and responses to immunotherapy compared to wild-type tumors, despite higher PD-L1 expression. 5c).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, innovative trial designs are critical for future clinical pharmacogenomic research efforts and will likely include the use of pragmatic studies, quality improvement projects, well‐designed retrospective studies, and meta‐analyses. A multitude of evidence, rather than a single RCT, will likely be needed to demonstrate the value of clinical pharmacogenomics . Such evidence will also be essential in expanding reimbursement models and advancing the roles and responsibilities of clinical pharmacists in pharmacogenomics.…”
Section: Clinical Pharmacogenomics Researchmentioning
confidence: 99%